Efficacy of biocontrol agents against damping-off and Sclerotinia stem rot diseases and their role in eliciting defense in chickpea plants - Yaser H. El-Gammal; Salama A. S. El-Blasy; Neamat A. M. Khalifa; Shereen Abu El-Maaty; Sara B. H. Awaly (Egyptian Journal of Biological Pest Control)
Abstract Background Chickpea (Cicer arietinum L.) is the third most important pulse crop grown worldwide. Sclerotinia sclerotiorum causes damping-off and stem rot diseases, leading to significant economic losses in chickpea crop yield. Biological control has proved to be an effective alternative for managing plant diseases. Results These pathogenic fungi were isolated from different governorates in Egypt and differed in terms of their pathogenicity on Giza 3 cv.-chickpea plants in vivo. S. sclerotiorum Sakha-S1 with accession No. (PQ558663) was the most aggressive isolate. Trichoderma atroviride was the most effective fungal bioagent in vitro since recorded the highest S. sclerotiorum growth decrease, followed by T. hamatum and T. harzianum; meanwhile, Serratia sp. was the least effective isolate. In greenhouse conditions, Topsin M-70® emerged as the most successful treatment for reducing disease prevalence. Combinations of microbial bioagents specifically all four (T. atroviride, Pseudomonas fluorescens, Bacillus polymyxa, and Serratia sp.) and a combination of three (P. fluorescens, B. polymyxa, and Serratia sp.) followed in effectiveness. Serratia sp. applied alone proved to be the least effective treatment. The same results were obtained in a two-year field study (2020–2021 and 2021–2022) and assessed the impact of various treatments on chickpea disease, growth, and yield components. Interestingly, all the microbial bioagents substantially enhanced chickpea growth parameters, including plant height, number of branches per plant, number of capsules per plant, number of seeds per plant, seed weight per plant, average weight of 100 seeds, and overall chickpea yield. The role of these microbial bioagents in the defense of oxidation enzymes (Peroxidase, polyphenol oxidase, and catalase) associated with defense-related genes (ABR18, PRP, and PR-4) which shown notable variations in gene expression levels of defense-related genes due to treated with various microbial bioagents after 14 days from application. All three genes were up-regulated in combinations including (P. fluorescens + Serratia sp.), (T. atroviride + P. fluorescens), and (T. atroviride + Serratia sp.), demonstrating a collaborative impact on defense gene expression. Conclusion The study investigated the effectiveness of microbial bioagents against chickpea stem rot disease, their role in the defense of oxidation enzymes and defense-related genes, and their impact on growth and yield components. It will focus on producing commercial biofungicides to minimize the use of fungicides.